Indian reserves in Nova Scotia and Prince Edward Island - Canada. Surveys and Mapping Branch ([Department of Mines and Technical Surveys Canada], 1965)
This is a general map of Nova Scotia and Prince Edward Island in 1965 showing roads, railways, trails, parks, First Nations reserves, cities and towns. Stamped on map: Canada Lands Surveys records 52339, 23 April, 1965. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Scale 1:500,000, or 7.89 miles to 1 inch. Relief shown pictorially and by spot heights. Transverse Mercator projection, central meridian 63°. Shows roads, railways, trails, parks, First Nations reserves, cities and towns.